KEPASTIAN HUKUM DALAM EKSEKUSI BARANG BUKTI TINDAK PIDANA NARKOTIKA (STUDI TERHADAP PUTUSAN MAHKAMAH AGUNG NO.1258.K/PID.SUS/2014 DAN PUTUSAN NO. 14/PDT.PLW/2014/PN.STB) - Muhammad Husairi; Sunarmi Sunarmi; Madiasa Ablisar; Mahmud Mulyadi (Universitas Sumatera Utara, 2017)
ABSTRACT For the authority of the prosecutor in the criminal field concerning the executor is an act of prosecution as an executor of carrying out the determination of judges and judicial decisions has permanent legal force. Evidence in criminal activities are often decided in court for the deprived, but there is something different in narcotic crime, namely Article 101 of Law Number 35 Year 2009 on Narcotics. The method used in this research is normative. The formulation of the problem is how the prosecutor’s role in the execution of criminal decisions? How is the execution of the evidence relating to the third party in narcotic cases in the District Court of Stabat and what barriers exist to the execution? How consideration of the judge of the Supreme Court Decision No. 1258.K / Pid.Sus / 2014 and Decision of the Civil District Court Stabat No. 14 / Pdt. Plw / 2014 / PN. STB. The role of prosecutors in the execution of criminal decisions, when referring to Article 101 of Law Number 35 Year 2009 on Narcotics, namely (1) Narcotics, Narcotics Precursor, and tools or goods used in the crime of Narcotics and Narcotics Precursor or concerning Narcotics and Precursors narcotics and results expressed seized for the state. (2) In terms of the tools or items seized as referred to in paragraph (1) is the property of third parties acting in good faith, the owner may appeal against the confiscation to the respective court within 14 (fourteen) days after the announcement of the court decision level first. Shows that legal uncertainty in the execution of narcotic crime evidence by the Attorney. Consideration of the judge in the District Court Stabat related narcotic crime evidence of a third party in this case the consideration of the judge is still stiff. Judges still refers to in paragraph (1) of Article 101 of Law Number 35 Year 2009 on Narcotics without seeing paragraph (2). Obstacles encountered in the execution of narcotic crime evidence is in the case of criminal decisions, in which the civil verdict filed a third party is granted by the judge, so the Attorney as executor experiencing difficulties. Consideration of the judge’s ruling in Supreme Court Decision No. 1258.K / Pid.Sus / 2014 shows that in this case the judge is too rigid in its decision without considering information from third parties that the evidence revealed that the car used by the offender is a hired car (rental) from third parties. In a civil ruling No. 14 / PDT.PLW / 2014 / PN.STB decided won third party claim. Supposedly when the judges on criminal decisions observant and careful in its consideration of third party certainly does not need to be a civil lawsuit. It would need to Attorney General of the Republic of Indonesia issued Decree Attorney General on the execution of the evidence, so that the execution evidence narcotic crime obtain legal certainty. It would need to judge in court viewed the evidence carefully and thoroughly and consider the injured third party so that the execution of the evidence does not cause problems. It would need to Attorney General and the Supreme Court did MOU related to evidence in the criminal act of narcotics so that the problem of execution as evidence at a leter date is not an issue and the Supreme Court also issued SEMA and PERMA or related to it. Keywords: Rule of Law, Execution of Evidence, Narcotics.